Ultrasound evaluation of fetal gender at 12-14 weeks - Lubusky, Marek; Studnickova, Martina; Skrivanek, Ales; Vomackova, Katherine; Prochazka, Martin (Biomedical papers, 2012)
Aims: The aim of this study was to assess the feasibility and accuracy of fetal gender assignment by transabdominal ultrasound at 12-14 weeks of gestation.Methods: Fetal gender assessment was performed in 1222 singleton pregnancies. In all fetuses the crown-rump length (CRL) was measured and the genital area of the fetus was examined in the mid-sagittal plane. The result of ultrasound examination was compared to the phenotypic sex of the newborn after delivery.Results: The feasibility as well as accuracy in determining gender increased with growing fetal CRL. At CRL < 50 mm (gestational age < 11+4) the feasibility was 39.1% and accuracy 30.5% (40.9% in male gender vs 24.3% in female gender). At CRL 50-54.9 mm (gestational age 11+4 to 12+0) the feasibility was 63.5% and accuracy 75.0% (89.1% in male gender vs 66.7% in female gender). At CRL 55-59.9 mm (gestational age 12+0 to 12+2) the feasibility was 90.5% and accuracy 96.6% (99.1% in male gender vs 93.5% in female gender). At CRL ≥ 60 mm (gestational age ≥ 12+2) the feasibility was 97.4% and accuracy 100.0% (100.0% in male gender vs 100.0% in female gender).Conclusions: Fetal gender may reliably be determined when CRL ≥ 60 mm (gestational age ≥ 12+2). Male gender may already be reliably determined when CRL ≥ 55 mm (gestational age ≥ 12+0). If CRL < 50 mm (gestational age < 11+4) the gender cannot be reliably predicted.
Keywords: fetal gender; fetal sex; first trimester; ultrasonography